Human resources endowment and the work performance of the workers of the health network - Huancavelica, 2017 (GnosisWisdom, 2022)
The research work called “Endowment of human resources and work performance of workers of the Health Network - Huancavelica, 2017”, whose general objective was “to determine the relationship between the provision of human resources and the work performance of the workers of the health network - Huancavelica, 2017”, for which the following methodology was used: the research was applied at a correlational level, non-experimental design, the survey was used as a technique and the questionnaire as an instrument, the population and the sample was made up of 54 workers from the Huancavelica health network, with whom the following results were reached: positive and significant correlations were obtained between the dimensions of planning, job design, recruitment, selection and the variable labor performance of workers with values of 0.318; 0.391, 0.323 and 0.394 respectively, so the overall correlation was positive and significant with a correlation index value of taenda kendall of 0.636, in addition 100% of respondents had negative perceptions for both study variables; With what came to the following conclusions: the provision of human resources has a high relationship with the variable labor performance of the workers of the Huancavelica health network, being so much planning, job design, recruitment and selection in the Provision of resources are key points for a good work performance of workers
Keywords: Work performance; Planning; Job design; Recruitment and selection